Linguistics as a Science - Yngve, Victor H. (Indiana University Press, 1986)
This pathbreaking work lays a new foundation for linguistics: It focuses on people rather than on language and is governed by science rather than grammar or philosophy. A linguistics built on this foundation avoids many intellectual problems, it can confront the full observational details of how people communicate, and provides greater relevance to studies in psychology, sociology, culture, and literature. The goal is nothing less than to provide the basis for a new scientific linguistics. The thesis that grammar and science are incompatible is developed in a carefully reasoned argument that explores the ancient foundations of grammar and considers the widely accepted goals of modern scientific linguistics. Out of this comes the insight that linguistics must choose between being a discipline of pure grammar that studies language as an abstract relation between sound and meaning and rejects science or a scientific discipline that studies people and how they communicate as part of the physical world. Professor Yngve lays out a new and formal notational apparatus capable of confronting in detail all the evidence of how people communicate . His approach provides formal methods suitable for studying previously difficult pragmatic, contextual, and variational phenomena. And it promises to provide greater relevance to adjacent disciplines, such as physiology, psychology, anthropology, sociology, semiotics, cultural and literary studies.